1995
DOI: 10.1002/bmc.1130090102
|View full text |Cite
|
Sign up to set email alerts
|

Gas chromatographic determination of enantiomers as diastereomers following pre‐column derivatization and applications to pharmacokinetic studies: A review

Abstract: The introduction of chiral chromatographic methods has revolutionized the art of separation and quantitation of chiral drugs in biological fluids. A large number of chiral derivatization reagents for various functional groups are available commercially. Therefore, pre-column derivatization methods have become attractive and simple for the gas chromatographic assays in biological fluids. The intent of this article is to review the pre-column chiral derivatization reagents employed in gas chromatographic separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 73 publications
0
9
0
Order By: Relevance
“…A survey of chiral derivatization reagents for GC and their application to various compound classes including applications to pharmacokinetic studies is given by Srinivas et al [271].…”
Section: Indirect Separationmentioning
confidence: 99%
See 2 more Smart Citations
“…A survey of chiral derivatization reagents for GC and their application to various compound classes including applications to pharmacokinetic studies is given by Srinivas et al [271].…”
Section: Indirect Separationmentioning
confidence: 99%
“…Most frequently used chiral derivatization reagents in GC are S(À) heptafluorobutyryl prolyl chloride, (À) menthyl chloroformate, Sa-methoxy-a-trifluoromethylphenyl acetyl chloride, S(À)-trifluoroacetyl prolyl chloride and R-(À)-2,2,2-trifluoro-1-(9-anthryl) ethanol [271]. More recently applied derivatization reagents are isopinocampheylamine [272] and O,O 0 -(R,R)-diacylated tartaric acid anhydrides [273].…”
Section: Indirect Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey of the literature reveals that there are very few reported methods for the determination of ETD in biological fluids, pharmaceutical formulations and in presence of its enantiomer. Of those studies reported, the techniques used include chromatography, HPLC [2][3][4][5], GC [6][7][8], in addition to spectrofluorimetric [9] and spectrophotometric methods [9][10][11]. However, an extensive survey of the literature revealed that there is no method available for the simultaneous determination of ETD in pure form and pharmaceutical formulations by oxidation-reduction reactions.…”
Section: Introductionmentioning
confidence: 99%
“…These methods typically employ gas chromatography coupled to mass spectrometry [10,11] and liquid chromatography with UV [12,13], fluorescent [14] or mass-spectrometric detection [15,16]. In cases when an achiral GC or LC column is used for the determination of enantiomeric excess, the mixture of enantiomers needs to be reacted with optically pure reagents prior to the analysis [17,18]. There are a number of agents available for pre-column derivatization, such as Mosher's acid [19][20][21], camphanic acid [22], perfluoro-2-propoxypropionylchloride [11] and others.…”
Section: Introductionmentioning
confidence: 99%